Structural and Functional Profiling of Water-Extracted Polypeptides from Periplaneta americana: A Multifunctional Cosmetic Bioactive Agent with Antioxidative and Anti-Inflammatory Properties - Xinyu Sun; Zhengyang Zhang; Jingyao Qu; Deyun Yao; Zeyuan Sun; Jingyi Zhou; Jiayuan Xie; Mingyang Zhou; Xiaodeng Yang; Ling Wang (Molecules, 2025)
Low-molecular-weight polypeptides (<3 kDa) were prepared from Periplaneta americana via enzymatic hydrolysis and ultrafiltration, yielding 3.53 ± 0.01 mg/g of peptide-rich extract. The extract was primarily composed of peptides, proteins, polysaccharides, phenolics, and flavonoids. HPLC-MS analysis identified 1402 peptide sequences, 80.51% of which were below 1000 Da, predominantly consisting of tri-, tetra-, and octapeptides. Monosaccharide profiling detected D-(+)-galactose, and quantitative assays determined the contents of total phenolics (12.28 mg/g), flavonoids (15.50 mg/g), proteins (85.84 mg/g), and total sugars (17.62 mg/g). The biological activities of the extract were systematically evaluated. The peptide fraction inhibited hyaluronidase activity by 58% at 5 mg/mL, suggesting protection of extracellular matrix integrity. In HaCaT keratinocytes, it promoted cell proliferation by 62.6%, accelerated scratch wound closure by 54%, upregulated Wnt-10b and β-catenin expression, and reduced intracellular ROS levels under oxidative stress. In LPS-stimulated RAW 264.7 macrophages, the extract decreased TNF-α, IL-6, and IL-1β production by 30%, 25%, and 28%, respectively, reduced MDA levels by 35.2%, and enhanced CAT and SOD activities by 12.3% and 60.3%. In vivo, complete closure of full-thickness skin wounds in mice was achieved by day 14. Safety evaluations using the chick chorioallantoic membrane assay and human patch tests confirmed the extract to be non-irritating and non-toxic. These findings highlight Periplaneta americana extract as a promising multifunctional bioactive ingredient for cosmetic and dermatological applications. Further studies on its active components, mechanisms of action, and clinical efficacy are warranted to support its development in skin health and aesthetic medicine.